Sensory information in children's statements of sexual abuse - Gérard Niveau (Oxford University Press, 2021)
The credibility of children's statements of sexual abuse is a controversial issue in forensic psychiatry and psychology. Neurobiological and clinical laboratory studies show that real memories contain more information regarding sensory details than false memories. The goal of the present field study was to evaluate whether sensory information was present in children's statements of sexual abuse, and whether this information was more often present in credible statements compared with non-credible statements. Sensory details were extracted from a sample of 96 statements of sexual abuse from children; 62 statements were considered credible and 34 statements were considered non-credible. This study showed that sensory information was present in 79% of children's reports of child sexual abuse. Sensory information was significantly more often present in statements considered credible compared with non-credible statements (85.5%, P < 0.001), but there were large variations in the sense involved. Logistic regression analysis showed that the presence of at least one sensory detail may be a good predictor of credibility (odds ratio, OR = 23.484, P < 0.05). It seems appropriate to include sensory details when assessing the credibility of children's statements of child sexual abuse, but it has not yet been demonstrated that use of such details significantly improves the validity of credibility assessments.